Health Promotion Behaviors of the Elderly participating in Activities and Excluding from Activities in Elderly School, Natamtai Sub-district, Mueang District, Trang Province - Sanee, Nuntaya; Sukkum, Worarat; Leartwanawattana, Janpen (Princess of Naradhiwas University Journal, 2023)
The purpose of this study was to compare health promotion behaviors of the elderly who participating in activities and those who exclude from activities in the elderly school located in , Natamtai Sub-district, Muang District, Trang province. The sample of the study consisted of a group of 56 seniors who attended the school and a group of 100 seniors who did not attend the school, selected by purposive sampling. A questionnaire was used to collected data which consisted of 2 parts; personal information and individuals’ health promotion behaviors. The questionnaire was verified by experts and received Cronbach 's alpha coefficient at 0.95. Data were collected between August to November 2019, and analyzed by descriptive statistics such as means, percentage, mean and standard deviation to evaluate both groups’ quality of life. Data were also analyzed for normal distribution and by independent t-test among groups with confidence interval of 95%. The results of the study showed that the health promotion behaviors of the elderly were at a high level. When categorizing in each aspect, it was found that the elderly who participated in activities had health promotion behaviors higher than and those who did not participate in the activities of the elderly schools with a statistical significance (p-value = .000, .001 and .000, respectively).